The Juridical Study Claims for Cancellation of Insurance Rights Auction Execution - Putri Qoriyati Aeny; Arpangi Arpangi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This study aims to examine the issue of the lawsuit for canceling the execution of credit guarantee auctions that are burdened with mortgage rights in the Boyolali District Court Decision Number 64/Pdt.G/2018/PN Byl. Reviewing Judges' Considerations in Deciding Cases on Claims for Cancellation of Execution of Mortgage Auctions. Reviewing the Legal Consequences of Lawsuits for Cancellation of Execution of Mortgage Auctions. This research is a normative juridical research. This research focuses on document or library research which essentially looks for theories, views that have correlation and are relevant to the problems to be studied. The results of the study concluded that the lawsuit for the cancellation of the execution of the credit guarantee auction that was burdened with mortgage rights in the Boyolali District Court Decision Number: 64/Pdt. G/2018/PN Byl, which starts with the provision of Local Credit Facilities (Current Accounts) with a credit limit not exceeding IDR 1,700,000,000.00 (one billion seven hundred million rupiah), based on Credit Agreement No. 125/PK/KRED/SLA/2008 dated October 13, 2008, and has been amended and updated several times, most recently by Amendment to Credit Agreement No. 145/AD/KRED/SLA/2015 dated October 6, 2015, and has been extended several times, most recently with the Notification of Extension of Period No. 145/AD/KRED/SLA/2015. 00118/SLA/SPPJ/2017 dated October 12, 2017. However, during the credit agreement period, the Plaintiff defaulted because he did not make installments every month, so Defendant I had given warning letters 3 times, therefore Defendant I through Defendant II carried out an auction execution of the object of credit guarantee that had been registered with the Mortgage Rights. The judge's consideration in deciding the lawsuit for the cancellation of the execution of the mortgage auction that was burdened with Mortgage was based on the exception of Defendant I and the evidence presented at the trial, which showed that the auction of the execution of the mortgage on the Collateral Object had been carried out in accordance with Article 22 PMK No. 27/PMK.06/2016, namely by the Class I Auction Officer at the Surakarta KPKNL is legally valid. The legal consequences of the Boyolali District Court Decision Number: 64/Pdt. G/2018/PN Byl that the auction of Mortgage Execution conducted by Defendant I and Defendant II of the collateral that is guaranteed by the credit agreement through the Surakarta State Property and Auction Service Intermediary Office (KPKNL) is legal according to law. The legal consequence for the Plaintiff is the obligation to pay court fees.